Pengaruh Sumber-Sumber Stres Kerja terhadap Kepuasan Kerja Pegawai Kecamatan Dringu Kabupaten Probolinggo - Yayuk Indah Wahyuning Tyas (Fakultas Ekonomi Universitas Panca Marga, 2015)
This study was conducted aims to understand the influence of sources job stress to satisfaction work of state civil apparatus , to understand the extent of the influence of sources job stress that is the design , demands the role of the demands between personal simultaneously to satisfaction work and to know variable of of the design will , demands the role of the demands between personal that have leverage most dominant to satisfaction work of state civil apparatus kecamatan dringu kabupaten probolinggo. This research the approach quantitative , as associative .Variable research used to research this is the independent variable ( sources job stress consisting of of the design , demands the role of the demands between personal and dependent variable ( satisfaction work ) .The method of analysis the data used to research is the quantitative analysis , with use of five formula that is the validity , reliability test , regression analysis linear multiple , test t ( partial ) and the f ( simultaneous ). Based on analysis on concluded that design work , demands role and demands between personal a partial significant work with satisfaction of state civil apparatus .While simultaneously . That design work , demands role , and demands between personal , influences work satisfaction of state civil apparatus in dringu kabupaten probolinggo .While variables most dominant affect satisfaction employment is between personal demands Key Words: The desain work, demani role, dermain between personal, work satisfaction